Preliminary study on birth weight and pre-weaning growth pattern in crossed Boer kids - M.Y., Syahirah; Mat, K.B; Rusli, N. D; C.H., Hasnita (Universiti Malaysia Kelantan, 2016)
This study was aimed to measure influence of some factors that involved in growth performance of crossed Boer kids including parity of mother, sex and litter size of kids. The data gained on body weight at birth weight (BW), 1 (Wt. 1), 2 (Wt. 2), and 3 (Wt. 3) months of age of 20 crossed Boer kids were recorded. There were two kids from does with parity 1, three kids from does with parity 2, eleven kids from does with parity 3, and four kids from parity ≥4. From all kids, eleven of them are male and nine female. Kids Six kids were born as single whereas eight kids were born as twin and six kids were born as triplet. Results showed that there was a no significant different (P>0.05) associated with parity of mother. For sex of kids, results show that highly significant differences (P<0.01) for body weight were identified at age one, two and three months. On the other hand, there was no significant difference (P>0.05) for body weight of kids due to single, twin or triplet kid born effect.